Determinants, impact, and association with heart failure therapies of heart failure readmission after transcatheter aortic valve replacement. (25th November 2020) - Auffret, V; Bakhti, A; Leurent, G; Bedossa, M; Sharobeem, S; Donal, E; Galli, E; Boulmier, D; Le Breton, H
Abstract: Aims: To evaluate the incidence, predictors, and impact of heart failure (HF) readmission within 1-year post-transcatheter aortic valve replacement (TAVR), and assess the effects of the prescription of guidelines-recommended therapies (i.e. renin-angiotensin system inhibitors, beta-blockers, mineralocorticoid receptor antagonists) at discharge on the risk of HF readmission and death. Methods and results: Patients included in the TAVR registry of a single expert centre from 2009 to 2017 were analysed. Competing-risk and Cox regressions were performed to identify predictors of HF readmission and death. Among 750 patients, 102 (13.6%) were readmitted for HF within 1-year post-TAVR. The 30-day incidence of HF readmission was 6.6%, 53 patients (7.1%) experienced late readmissions (>30 days post-TAVR), and 17 (2.3%) had multiple readmissions. Independent predictors of HF readmission included diabetes mellitus, chronic lung disease, previous acute HF, grade III or IV aortic regurgitation, and pulmonary hypertension both at discharge from the index hospitalisation but not guidelines-recommended therapies. Overall, HF readmission did not significantly impact all-cause mortality (HR: 1.36, 95% CI: 0.99–1.85). However, late (HR: 1.90, 95% CI: 1.30–2.78) and multiple HF readmissions (HR: 2.10, 95% CI: 1.17–3.76) were significantly associated with all-cause mortality. Prescription of RAS inhibitors at discharge was associated with a lower rate of all-cause mortality, especially among patients receiving doses of 25–<50% (HR: 0.67, 95% CI: 0.48–0.94), and 75–100% (HR: 0.61, 95% CI: 0.37–0.98) of the optimal daily dose. Conclusion: HF readmission is common within 1-year of TAVR. Late and multiple HF readmissions associate with an increased risk of long-term all-cause mortality. Baseline comorbidities (diabetes, chronic lung disease, previous acute HF) and echocardiographic findings at discharge (grade III or IV aortic regurgitation, pulmonary hypertension) identified patients at high-risk of HF readmission. Guidelines-recommended therapies did not significantly affect the 1-year risk of HF readmission. Funding Acknowledgement: Type of funding source: None